Leadership dynamics in primary healthcare delivery: A case of rural GP practice in Northeast England - Obinna Alo; Julie Leckenby; Ahmad Arslan (International Journal of Management, Economics and Social Sciences (IJMESS), 2022)
Due to ongoing debates on evidence-based management (EBMgt) in healthcare, there is an increasing research interest in the relationship between leadership support and operational excellence in the health care sector. The purpose of this study is to critically evaluate the ethical leadership behaviour of the general practitioners (GPs) and their practice manager (PM) in a health centre in the United Kingdom (UK). We adopted a mixed method and used five theoretical lenses - manipulation, putting self above others, responsibility avoidance, lack of flexibility, and belittling others - to examine these medical leaders' ethical behaviour and to match their ethical behaviours with their employees' expectations. Although there is strong evidence of ethical behaviour, which reflects the National Health Service (NHS) core values, there are strong evidence of unethical behaviours too. We therefore analysed the impact of these leaders' (un)ethical practices on their employees' motivation. The findings from this study could be used to improve ethical decision making, leadership support, and leadership development in healthcare. The paper's findings also contribute to the application of EBMgt in healthcare sector.
Keywords: I19; 330; Ethical leadership; empowering leadership; medical leadership; organisational performance; National Health Service